Female entrepreneurship in perspective: A methodological issue - Paola Paoloni; Gabriele Serafini (Administrative Sciences, 2018)
A methodological approach to the concept of female entrepreneurship concept has not yet been treated: is female entrepreneurship an individual or collective concept? Is it considered a social or natural variable? The purpose of this research is to clear up these alternatives, which are preparatory questions for any research into female entrepreneurship that wishes to measure its features and effects. The article starts with the proposal of an identification procedure, necessary to identifying the variables of female entrepreneurship. It proceeds by classifying the concept of female entrepreneurship into four different modes and discussing their characteristics. The originality of this research consists in its fourfold classification of the concept of female entrepreneurship, intended as a preparatory step prior to the analysis of its characteristics and measures.
Keywords: 350; female entrepreneurship; entrepreneurship; economic variable classification